2019
DOI: 10.29332/ijpse.v3n1.239
|View full text |Cite
|
Sign up to set email alerts
|

The geoportal as strategy for sustainable development

Abstract: Ecuador is committed to venturing into the local development model based on the adequate use of endogenous resources and human potential in the community scenario; but the lack of reliable information associated with the inventory and availability of these resources in the localities does not favor the integrated participation of local actors in the planning and management of social development. The work shows what is related to the design and proposal of a geoportal for sustainable development in the province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
(3 reference statements)
0
4
0
2
Order By: Relevance
“…The implications of the Covid-19 pandemic, as analyzed by Aivaz and Micu (2021), have further highlighted the role of demographic variables in shaping perceptions, particularly in relation to the digital divide along age lines. In the digital realm, Gamez et al (2019) found that younger respondents, due to their higher digital literacy, were more engaged with digital tools like geoportals, thereby enhancing their involvement in sustainable development initiatives. However, older respondents, who might be less digitally literate, faced challenges in using such tools, potentially limiting their participation in sustainable development efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implications of the Covid-19 pandemic, as analyzed by Aivaz and Micu (2021), have further highlighted the role of demographic variables in shaping perceptions, particularly in relation to the digital divide along age lines. In the digital realm, Gamez et al (2019) found that younger respondents, due to their higher digital literacy, were more engaged with digital tools like geoportals, thereby enhancing their involvement in sustainable development initiatives. However, older respondents, who might be less digitally literate, faced challenges in using such tools, potentially limiting their participation in sustainable development efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Геопорталы как внешний компонент цифровых инфраструктур пространственных данных (ИПД) относятся к классу распределенных веб-систем и, следовательно, наследуют их характерные особенности. В частности, этот факт накладывает отпечаток на нефункциональные требования, предъявляемые к геопортальным системам [1] Качественное требование масштабируемости определяет способность геопортальной системы отвечать на вызовы роста функциональности и увеличения рабочей нагрузки [2]. При этом целесообразно, чтобы время поиска по базам геопространственных данных не росло экспоненциально при увеличении объема накапливаемой информации о природно-социально-производственных системах, а величина использования ресурсов не увеличивалась бесконтрольно с ростом количества пользователей.…”
Section: Abstract: Spatial Data Infrastructure Geoportal Performance Analysis Optimization High-load Systemsunclassified
“…Одним из необходимых условий принятия эффективных решений при управлении сложными территориальными объектами является своевременная выработка опережающих управленческих решений на базе прогнозных оценок состояния исследуемого объекта [1]. Актуальной задачей, имеющей важное экономическое и социальное значение, является пред-упреждение негативных последствий паводков в период весеннего половодья [2].…”
Section: Abstract: Spatial Data Infrastructure Geoportal Emergency Monitoring Water Level Forecastingunclassified